2009
DOI: 10.2478/fhort-2013-0130
|View full text |Cite
|
Sign up to set email alerts
|

The effect of calcium carbonate and top dressing with Peters Professional Special on the growth and flowering of Helleborus lividus Aiton

Abstract: For two years (2006 − 2007), seedlings and young plants of Helleborus lividus Aiton were grown in containers with a peat substrate, which was deacidified with calcium carbonate at the following doses: 2.5, 5.0, 7.5 and 10.0 g dm-3. The plants were divided into two groups in each variant of CaCO3 dosage, one fertilized with a solution of a lower (0.1%) and the other with a higher (0.3%) concentration of Peters Professional PL Special (15:11:29). Helleborus lividus growth in the first year of cultivation depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…Our findings revealed that number of leaves per plant was significantly decreased by the higher concentrations (10% and 20%). Szczepaniak et al [38] and Henschke et al [39] exposed Helleborus lividus Aiton and Helleborus orientalis Lam plants to higher concentrations of CaCO 3 and found a reduction in number of leaves per plant, although they did not find statistical differences between the treatments. Our results also showed that CaCO 3 had a positive effect on leaf Ca concentration.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Our findings revealed that number of leaves per plant was significantly decreased by the higher concentrations (10% and 20%). Szczepaniak et al [38] and Henschke et al [39] exposed Helleborus lividus Aiton and Helleborus orientalis Lam plants to higher concentrations of CaCO 3 and found a reduction in number of leaves per plant, although they did not find statistical differences between the treatments. Our results also showed that CaCO 3 had a positive effect on leaf Ca concentration.…”
Section: Discussionmentioning
confidence: 98%
“…The fluctuations and declines in plant height, especially evident under 5%, 10%, and 20% concentrations during incubation, may be attributed to fluctuations in soil pH and EC, impacting nutrient availability. Supanjani et al [25], Szczepaniak et al [38], Henschke et al [39], and Jessop et al [40] all agreed that higher concentrations of CaCO 3 significantly decreased plant height. Stunted growth is one of the primary symptoms in plants suffering from inadequate nutrition in calcareous soils [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Чтобы решить эту проблему, мы в Ботаническом саду имени Н.В. Цицина пересадили морозники в контейнеры, в литературе подобный опыт выращивания морозников для России еще не был описан, но есть опыт выращивания H. lividus [13].…”
Section: электронный научно-производственный журналunclassified
“…Horticultural producers select species with small thermal requirements and a short production cycle. For this reason, the importance of hellebores has increased recently, as different studies, including cultivation trials, have been conducted on this species [1][2][3][4][5][6]. Hellebores are herbaceous perennials in which flowering may be accelerated during a culture period of as little as 4-6 weeks in a greenhouse at a temperature of [12][13][14][15][16] o C for a very attractive season, i.e.…”
Section: Introductionmentioning
confidence: 99%